2020
DOI: 10.1088/1361-6641/ab7ce7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drain doping engineering on ambipolar and high-frequency performance of ZHP line-TFET

Abstract: In this paper, we present a new Z-shaped line tunnel field effect transistor (TFET) employing drain doping engineering with a split drain structure (SD-ZHP-TFET). The split drain (SD) approach in the proposed ZHP-TFET helps increasing tunneling width at the channel-drain interface, reducing ambipolarity. Moreover, a horizontal pocket (HP) is implanted in the source region to boost the ON-current of the proposed SD-ZHP-TFET structure. The effect of both these approaches in the line-TFET provides higher ON-curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The 2D schematic of the Ge-source SD-ZHP-TFET is shown in Figure 1(A) and this architecture is similar to existing literature. 31 The 2D view of SD-ZHP-TFET and ZHP-TFET are portrayed in Figure 1(B,C), respectively. It is well known that the energy bandgap of Ge is comparatively lower as compared to Si material.…”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The 2D schematic of the Ge-source SD-ZHP-TFET is shown in Figure 1(A) and this architecture is similar to existing literature. 31 The 2D view of SD-ZHP-TFET and ZHP-TFET are portrayed in Figure 1(B,C), respectively. It is well known that the energy bandgap of Ge is comparatively lower as compared to Si material.…”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
“…The dimensions of t r1 and t r2 are equal and it is denoted by t u . A large of number of TFET structures with gate oxide thickness of 1 and 2 nm are reported 21,24,31 in literature. Accordingly, in this work a gate oxide thickness of 1 nm is considered for Ge-source SD-ZHP-TFET.…”
Section: Device Structure and Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…19 Nawal and Chauhan reported that TFET with hetero dielectric BOX has improved RF and analog behavior compared to conventional TFET. 20 Likewise, the RF/analog characteristic of a Z shape line TFET (ZS-TFET) having split drain engineering is examined through TCAD simulator 21 and TFET with split drain has improved cut-off frequency compared to ZS-TFET. On the other hand, the fabrication of non-traditional TFET architecture is a very critical job.…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel FET is one of the evolving energy-efficient devices to substitute bulk MOS in the low supply voltage regime due to its capability to achieve a sub-60 mV/decade inverse subthreshold slope in room temperature [1][2][3][4][5][6]. The TFET devices heavily rely on the interband tunneling mechanism for its carrier transportation and thus exhibit improved switching characteristics at ultra-low supply voltage [1,2].…”
Section: Introductionmentioning
confidence: 99%